PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM IMPLEMENTASI APLIKASI PERPUSTAKAAN DIGITAL BERBASIS ANDROID - Nourma Ayu Sulistiyowati; Definka Puan Shalika Abdillah; Yusuf Nurrahman; Darsinah Darsinah; Wafroturrohmah Wafroturrohmah (STKIP Pesisir Selatan, 2026)
This study aims to examine the role of school leadership in implementing an Android-based digital library application (iPERPUS) at SMP Negeri 1 Karangmalang. A qualitative case study approach was employed, with data collected through observations, interviews with the principal, teachers, and students, as well as document analysis. The data were analyzed using an interactive process involving data reduction, data presentation, and conclusion drawing. The findings indicate that the successful implementation of iPERPUS was strongly influenced by the principal’s leadership through institutional policy development, strategic decision-making, digital literacy promotion, infrastructure support, and stakeholder collaboration. The adoption of free platforms within the Google Workspace ecosystem enabled the development of a sustainable and cost-efficient digital library without substantial technological investment. The implementation of iPERPUS improved access to learning resources, strengthened digital literacy, enhanced cost efficiency, and increased the involvement of teachers and parents. However, several challenges remained, including internet connectivity limitations, content updating, and restricted features of free platforms. Overall, the study demonstrates that effective school leadership plays a pivotal role in driving digital transformation and ensuring the successful implementation of innovative digital library initiatives in schools.